2000
DOI: 10.1128/jvi.74.8.3881-3887.2000
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Novel Cellular Homolog of Interleukin-10, AK155, by Transformation of T Lymphocytes with Herpesvirus Saimiri

Abstract: Although herpesvirus saimiri-transformed T lymphocytes retain multiple normal T-cell functions, only a few changes have been described. By subtractive hybridization, we have isolated a novel cellular gene, ak155, a sequence homolog of the interleukin-10 gene. Specifically herpesvirus saimiri-transformed T cells overexpress ak155 and secrete the protein into the supernatant. In other T-cell lines and in native peripheral blood cells, but not in B cells, ak155 is transcribed at low levels. AK155 forms homodimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
190
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(195 citation statements)
references
References 48 publications
3
190
0
Order By: Relevance
“…The gene sequence, on discovery, differed from the already known genomic sequence AC007458 with four point mutations and one deletion of three nucleotides (nt) in the 5 0 region, and nine point mutations, one insertion of three nt and one deletion of six nt in the large third intron. 19 In the database dbSNP (www.ncbi.nlm.nih.gov/SNP/) several other variations are reported for both the 5 0 and third intron sequences. Though the coding sequence of the IFN-g gene is strongly conserved, several SNPs are dispersed over the promoter region as well as over the intronic and the 3 0 untranslated regions of the gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene sequence, on discovery, differed from the already known genomic sequence AC007458 with four point mutations and one deletion of three nucleotides (nt) in the 5 0 region, and nine point mutations, one insertion of three nt and one deletion of six nt in the large third intron. 19 In the database dbSNP (www.ncbi.nlm.nih.gov/SNP/) several other variations are reported for both the 5 0 and third intron sequences. Though the coding sequence of the IFN-g gene is strongly conserved, several SNPs are dispersed over the promoter region as well as over the intronic and the 3 0 untranslated regions of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Its function is not yet known. 19 IL-22 expression is inducible in T-cells and mast cells, and may have a role in inflammation and neurobiology. 20,21 Another gene, MDM-1, is the human homologue of the mouse double-minute-1 gene (mdm-1), a gene amplified strongly in transformed mouse cells containing numerous doubleminute particles.…”
Section: Introductionmentioning
confidence: 99%
“…41 Second, a novel cellular gene ak155 (IL-26) was identified, which is overexpressed by HVS C488-transduced cells and the product of which (IL-26) is also secreted from the cells. 34 We wanted to know whether IL-26 and Lyn are also overexpressed in RT-and Dorf1RT-transduced T cells. Therefore WT f -, RT-, Dorf1RT-and mock-infected T cells were harvested 1, 3 and 5 weeks post infection (wpi), whereby the Dorf1RT-and mock-infected cells needed the restimulation with irradiated feeder cells at 3 wpi.…”
Section: Expression Of Htert Il-26 and Lyn In Transduced T Lymphocytesmentioning
confidence: 99%
“…These virus mutants carry the hTERT expression cassette at the right end of the L-DNA and with or without the stpC/tip gene (orf1) at the left L-DNA end. As HVS-transduced T cells exhibit a few specific properties such as CD2 hyperreactivity, 33 elevated IL-26 34 and Lyn expression, 19,35 we analyzed the influence of the stpC/ tip deletion (Dorf1) on these properties and concluded that hTERT could not substitute them in this phenotype, although hTERT was functionally expressed after transduction. The interaction of StpC with Ras and tumor necrosis factor-associated factors leading to nuclear factorkB activation, in addition to the association of Tip with signal transducers activators of transcription and tipassociated protein, are crucial for the facilitated growth transformation of human T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Within this subfamily, IL-19, IL-20 and IL-24 share receptor complexes; 6 all of them are capable of signaling through IL-20R1/IL-20R2 and IL-20 and IL-24 can also use IL-22R/ IL-20R2. 6 Because a growing number of studies have revealed the association of IL-19, 7-9 IL-20 8,[10][11][12][13][14][15][16] and IL-24 [17][18][19][20][21][22] with diseases, the identification of soluble proteins derived from the genes of the functional receptors may provide more insights into the biomolecular mechanisms of their functions.…”
Section: Introductionmentioning
confidence: 99%